Concept of Restitution Application as a Form of Corporate Criminal Liability in Law Enforcement towards Human Trafficking Criminal Act - PARAMUDHITA, H Radea Respati; SUSENO, H. Sigid; SULISTIANI, Lies (Journal of Advanced Research in Law and Economics, 2020)
This research aims to analyze: (1) the corporate liability as a law subject in terms of human trafficking criminal act; and (2) the concept of restitution application as a form of corporate criminal liability in the case of law enforcement towards human trafficking criminal act. This research is categorized as normative legal research through the statue and conceptual approaches. The result of the research found that: (1) in terms of criminal law, both seen from the Law of Human Trafficking or theories of corporate liability, corporate is one of law subject in terms of human trafficking criminal act whose liability can be asked regarding human trafficking criminal act. The corporate liability which conducts human trafficking criminal act can be determined through the fulfillment of general criminal liability terms (subjective terms) including the presence of liability, the presence of guilt both intentionally and negligence, and the absence of reasons to omit the criminal law. The form of liability of corporate criminal in terms of human trafficking criminal act can be decided precisely using vicarious liability; and (2) restitution application concept, as a form of corporate criminal liability in law enforcement towards the human trafficking criminal act so that justice principle, legal certainty and benefit for the victim of human trafficking. Therefore, the concept offered is first, fulfillment of material rights. Second, the availability of legal protection accompanied with its implementing which is a very urgent matter. Third, the availability of structure (in the form of institution/entity) and infrastructure is an essential thing in process managing, deciding and executing the human trafficking criminal act.